Does a nitrogen matter? Synthesis and photoinduced electron transfer of perylenediimide donors covalently linked to C59N and C60 acceptors1. Issue 16 (28th April 2015) - Martín-Gomis, Luis; Rotas, Georgios; Ohkubo, Kei; Fernández-Lázaro, Fernando; Fukuzumi, Shunichi; Tagmatarchis, Nikos; Sastre-Santos, Ángela
<x xml:space="preserve">Abstract</x> Photoexcitation of PDI in both PDI-C59N and PDI-C60 results, by photoinduced electron transfer, in formation of long-lived charge-separated states with a lifetime of 400 ps for the former and 120 ps for the latter dyads, respectively.